Methodology of the polyoptimization for spatial processes - Biłozor, Andrzej; Renigier-Biłozor, Małgorzata (International Conference “Environmental Engineering”, 2017)
Optimization is a complex activity that aims to find the best solution for a given activity, considering all existing limitations. The best variant possible in the set of acceptable variants is sought-out. In particular, in urban areas, optimization of land use function as the beginning of a decision-making process requires performing a great number of tasks, which minimize the risk of spatial conflicts, set at the stage of studies and analyses. Polyoptimization is optimization with a vector objective function. The aim of polyoptimization is to find the best solution, concurrently applying several criteria which, due to their limitations, are conflicting as a general rule. It leads to finding compromise solutions (polyoptimum variants in the set of acceptable variants). In the paper the following ideas will be presented – the idea of spatial processes polyoptimization, the methods for determining the collection and selection of compromise solutions, the methodology for determining polioptimum states of the space use, the possibility of using polyoptimization methods that are regarded as supporting decision-making tools in the planning and management of space with the use of GIS tools. The Authors will show the benefits of using the polyoptimization. The methods of formulating and solving problems which are related to selection of optimum way use of land will be delivered.
Keywords: optimization; polyoptimization; spatial processes